Beggaring thy neighbor at the state and local level. Issue 4 (7th November 2016) - Murphy, Ryan H.
Abstract : Purpose: This paper aims to address a growing empirical literature which measures the size of the fiscal multiplier at the state and local levels. This literature generally fails to consider the reaction function of the central bank, which typically should be expected to offset local increases in spending by reducing it elsewhere in the currency area. This is true under rather orthodox assumptions, such as an inflation targeting central bank meeting its target. Design/methodology/approach: The author reviews prominent examples of the literature and establishes the extent to which the empirical methodology avoids the issue he raises. Subsequently, the author discusses its importance. Findings: Certain papers in the literature, especially Nakamura and Steinsson (2014), are careful about the issue. Most papers reviewed, however, are not. Practical implications: There are severe limitations to papers using these methodologies. They are either contingent on very specific assumptions regarding central banks or lack policy relevance. Earlier methodologies, such as vector autoregression and the "narrative" method, deserve higher relative credence among methodologies applied to studying the size of the fiscal multiplier. Originality/value: The current literature either entirely ignores the issue raised here or it is very briefly brushed aside. Considering the orthodoxy of the assumptions, at the very least, the issue deserves far greater recognition in the future. It may demand a broader re-evaluation of the family of methods.